2019
DOI: 10.1039/c8tb02962h
|View full text |Cite
|
Sign up to set email alerts
|

Emerging biomedical applications of polyaspartic acid-derived biodegradable polyelectrolytes and polyelectrolyte complexes

Abstract: A summary of positive biomedical attributes of biodegradable polyelectrolytes (PELs) prepared from aspartic acid is provided. The utility of these PELs in emerging applications such as biomineralization modulators, antimycobacterials, biocompatible cell encapsulants and tissue adhesives is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 130 publications
0
46
0
Order By: Relevance
“…The reactions catalyzed by phosphoric acid yield linear chain whereas uncatalyzed reactions lead to branching (Wolk et al, 1994). High temperature, high catalyst, and aspartic acid monomer concentration can significantly increase molecular weight (Mw) (Jalalvandi and Shavandi, 2018; Yavvari et al, 2019). Recent studies have also shown when phosphoric acid is utilized as both catalyst and polymerization media (aspartic acid monomer: phosphoric acid, 1:1), PASP with high Mw and reaction yield is achieved (Zakharchenko et al, 2011; Moon et al, 2013; Szilágyi et al, 2017).…”
Section: Synthesis Of Polyaspartic Acidmentioning
confidence: 99%
“…The reactions catalyzed by phosphoric acid yield linear chain whereas uncatalyzed reactions lead to branching (Wolk et al, 1994). High temperature, high catalyst, and aspartic acid monomer concentration can significantly increase molecular weight (Mw) (Jalalvandi and Shavandi, 2018; Yavvari et al, 2019). Recent studies have also shown when phosphoric acid is utilized as both catalyst and polymerization media (aspartic acid monomer: phosphoric acid, 1:1), PASP with high Mw and reaction yield is achieved (Zakharchenko et al, 2011; Moon et al, 2013; Szilágyi et al, 2017).…”
Section: Synthesis Of Polyaspartic Acidmentioning
confidence: 99%
“…Although the preparation of most types of poly(amino acid)s is expensive, the synthesis of PASP can be relatively cost-efficient, and it does not require extreme conditions, as we described previously [25,[37][38][39][40]. In the last decades, the interest of scientists in PASP-based hydrogels increased significantly due to their potential applications in medical, pharmaceutical and environmental fields [25,34,[41][42][43][44]. Several publications can be found concerning different types of cross-linkers to prepare PASP-based hydrogels [22,34,45].…”
Section: Introductionmentioning
confidence: 99%
“…The solid was dissolved in DMSO. The solution was dialyzed against water in a dialysis bag with a proper molecular cutoff and then solid m-PEG-b-PAsp was obtained by lyophilization (Yang et al, 2015;Yavvari et al, 2019).…”
Section: M-poly (Ethylene Glycol)-b-poly (Aspartate)mentioning
confidence: 99%